Developing low-cost two wheels balancing scooter using proportional derivative controller - Petrus Sutyasadi; Manukid Parnichkun (Institute of Advanced Engineering and Science, 2022)
This study suggests a strategy for creating a low-cost two-wheeled balancing scooter with a simpler system that can work similarly to the commercial ones on the market. A simple system will help people to understand how it works and how to build it. The mechanical parts were made from simple hollow bar iron. Wheelbarrow wheels were attached to two electric bicycle motors, and the controller was using an 8-bit microcontroller running a proportional derivative (PD) controller. PD controller only is not enough to run the scooter with a passenger smoothly. Some strategies were added to overcome some non-linear problems due to the use of low-cost components. Finally, the system is successfully built and can be ride by a 65 kgs weight of rider. The scooter can turn left or right, and even to make a 360-degree spot-rotation.